OVERPRESSURE MECHANISM ANALYSIS AND 3D PORE PRESSURE MODELING IN THE DEEP ZONE, HANDIL FIELD, LOWER KUTAI BASIN, EAST KALIMANTAN - HESRON SURBAKTI (NIM: 22015319), AZARYA
The lower part of the Kutai Basin is a Tertiary basin in Indonesia that has proven to contain significant amount of hydrocarbon. One of gas production intervals targeted by drilling is Deep Zone in Handil Field which is experiencing overpressure condition. The purpose of this study is to model overpressure distribution in the Deep Zone and its relationship with the geological condition in the study area. This study is performed by integrating wireline log data, formation pressure test, mud log and drilling parameters, drilling report, and 3D seismic velocity data. The 3D seismic data is used to know the lateral distribution of overpressure zone. This study reveals that overpressure in the study area is generated by non-loading mechanism caused by source rock maturation. The top of overpressure is controlled by the presence of thick shale sequence, deposited in a pro-delta environment. Stratigraphically, this shale is located in MF12 marker which is Middle Miocene in Age. The blind well test shows that result of seismic velocity analysis can capture all phenomenon related to the presence of overpressure in the tested wells. Based on this circumstance, it is concluded that the modeling of overpressure distribution by using 3D seismic velocity data gives a reliable result.